Factors predicting sustainability of the schoolwide positive behavior intervention support model. Issue 2 (3rd April 2018) - Chitiyo, Jonathan; May, Michael E.
ABSTRACT: The Schoolwide Positive Behavior Intervention Support model (SWPBIS) continues to gain widespread use across schools in the United States and abroad. Despite its widespread implementation, little research has examined factors that influence its sustainability. Informed by Rogers's diffusion theory, this study examined school personnel's perceptions of the attributes of SWPBIS that predict its sustainability. These attributes include relative advantage, compatibility, complexity, trialability, and observability. Participants were school personnel employed in schools implementing SWPBIS. Results indicated that the relative advantage and observability of SWPBIS may predict its sustainability. These results led to some important implications for practitioners involved in the implementation of the SWPBIS. Limitations and recommendations for future research are also provided.